Baccharis dracunculifolia DC. (Asteraceae): composição do óleo essencial, diversidade e parâmetros genéticos - Belini, Camila Moreira Batista [UNESP] (2015)
The Baccharis dracunculifolia species can be used in the recovery of deforested areas and disturbed by agricultural activities in addition to providing many health benefits, but there are no germplasm collections of seeds and seedlings to meet this demand, which may result in inadequate exploitation of the species as it happened to Baccharis trimera. In this context, the purpose of this work is to provide subsidies for the sustainable exploitation of the species, as well as the development of genetic improvement for essential oil production and the formation of a germplasm bank of seeds with wide genetic variability. The plant materials used for this study were divided into two groups, were collected in an altitudinal gradient, plant natural populations in Campos do Jordão, Ubatuba, and Campinas. 56 constituents were found in the essential oil composition, extracted by hydrodistillation, natural populations studied in the years 2012 and 2013, with only eight constituents common to all populations, the trans-nerolidol compound was the major substance for all populations (ranging from 21.6 to 40.8%), These populations are well structured chemically suggesting that there is the influence of altitude, especially for the chemical compounds of the population of Campos do Jordão. In the other group, it was a test provenances and progenies installed in CPQBA/UNICAMP, in which it evaluated the essential oil yield extracted by distillation by steam distillation of water and fresh mass of shoots for the estimation of genetic parameters, the yield ranged from 0.1% to 0.3%, and no significant differences were observed between the averages. The yield of essential oil kg/1000 m2 on average, ranged from 13 to the population of Campinas 15 for the population of Ubatuba. The characteristic of weight, on average, the progeny was higher for the population of Campinas (1.6 kg), followed by Ubatuba ...